Treatment of cutaneous vasculitis - Micheletti, Robert G. (Frontiers in Medicine, 2022)
Cutaneous vasculitis encompasses a spectrum of disease states, with varied morphology, severity, and potential for systemic involvement. Even vasculitis which is skin-limited can have a significant quality-of-life impact, necessitating treatment. This manuscript summarizes the available evidence for management of various types of skin-limited vasculitis and provides a proposed therapeutic ladder based on published studies and expert opinion.